(3TgGOI GdELeGY aj YbGFO GdRjOjIs - (3GdbGVi TeS GdOjf LYaQ Hf CMeO Hf YHO GdSdGe GdjeGfi GdRjOis
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi SGHZ CaVGdg aEf HYV GdENhGf SCdfi Yf HjGf CUhd GdeSGFd GdCQHY s
(3BNQgG (B:s
(3hef cGf ZQVg GdeYGfOI hGdecGHQI de jQOYg GdcKjQ , hef Gddg SHMGfg CSJefM GdYUeI ef GdRdd , hGdJhajb ai Gdbhd hGdYed Je Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3GdJhMjO hGdedd hGdfMds